2008
DOI: 10.1073/pnas.0710018105
|View full text |Cite|
|
Sign up to set email alerts
|

EB1 promotes Aurora-B kinase activity through blocking its inactivation by protein phosphatase 2A

Abstract: EB1 (end-binding protein 1) is a key player in the regulation of microtubule dynamics. In concert with its binding partners, adenomatous polyposis coli and p150 glued , EB1 plays a crucial role in a variety of microtubule-based cellular processes. In this study we have identified in a yeast two-hybrid screen the mitotic kinase and chromosome passenger protein Aurora-B as a binding partner of EB1. GST pull-down and immunoprecipitation experiments reveal a specific interaction between Aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(89 citation statements)
references
References 26 publications
3
86
0
Order By: Relevance
“…One of these could be the cyclin-dependent kinase CDKA;1, previously shown to decorate the late PPB and to induce its disassembly [39][40][41][42] , and which co-purified with TON1 in TAP experiments 43 . Aurora kinases, which in animals are functional antagonists of PP2A at the centrosome and microtubule plus ends [44][45][46] , are also putative candidates as suggested by recent results pointing to a function for Aurora kinases in premitotic division plane orientation and cortical cytoskeleton organization 47,48 . Besides a role in PPB formation, the TTP complex likely has a role in interphase cortical array organization as well.…”
Section: Discussionmentioning
confidence: 95%
“…One of these could be the cyclin-dependent kinase CDKA;1, previously shown to decorate the late PPB and to induce its disassembly [39][40][41][42] , and which co-purified with TON1 in TAP experiments 43 . Aurora kinases, which in animals are functional antagonists of PP2A at the centrosome and microtubule plus ends [44][45][46] , are also putative candidates as suggested by recent results pointing to a function for Aurora kinases in premitotic division plane orientation and cortical cytoskeleton organization 47,48 . Besides a role in PPB formation, the TTP complex likely has a role in interphase cortical array organization as well.…”
Section: Discussionmentioning
confidence: 95%
“…The kinase activity of Aurora B is regulated by its phosphorylation level (25,26), and PP2A is a well-known negative regulator of Aurora B (26). Thus, depletion of PPP2R1A may enhance Aurora B activity by increasing its phosphorylation (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…PP2A binds and dephosphorylates Aurora B (25,26). To determine whether Aurora B is involved in the PPP2R1A depletioninduced phenotype, control luciferase siRNA or PPP2R1A siRNA was transfected with or without Aurora B siRNA to HeLa and Mad2-overexpressing HeLa cells, and then a colony formation assay was performed.…”
Section: Aurora B Sirna Decreases Mad2 Phosphorylation In Mitosis Andmentioning
confidence: 99%
“…Using Lamin B1 and DAPI staining, we demonstrated that the nuclear envelope was closed and chromosomes were decondensed (Figure 1B); however, in CLL doublet cells the cytoplasm was interconnected (Figure 1A). When we performed immunofluorescence staining for Plk1 and Aurora B, proteins known to regulate cytokinesis,11, 12 we found that Plk1 localized at the cytokinesis contractile ring in CLL doublets (Figure 1C), which is a hallmark of cytokinesis 11. Taken together, our results indicate that CLL cell doublets were in the cytokinesis stage of the cell cycle, specifically, after reformation of the nucleus, but before abscission and physical separation of the cytoplasm 11, 13, 14, 15, 16…”
Section: Resultsmentioning
confidence: 99%